2014
DOI: 10.1021/ac502627w
|View full text |Cite
|
Sign up to set email alerts
|

Application of Solid Phase Microextraction for Quantitation of Polyunsaturated Fatty Acids in Biological Fluids

Abstract: Development of a straightforward strategy for simultaneous quantitative analysis of nonesterified fatty acids (NEFA) species in biofluids is a challenging task because of the extreme complexity of fatty acid distribution in biological matrices. In this study, we present a direct immersion solid phase microextraction method coupled to liquid chromatography--mass spectrometry platform (DI--SPME--HPLC--ESI --MS ) for determination of unconjugated fatty acids (FA) in fish and human plasma. The proposed method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…37 Furthermore, fatty acids have an association constant (Ka) with albumin at 25 C (9.2 × 10 4 to 4.3 × 10 5 M −1 ) that is higher than that of uremic toxins (0.98 × 10 5 M −1 ), allowing them to have a stronger connection with HSA. 38,39 Indeed, de Loor et al 40 observed that when sodium octanoate (a medium chain fatty acid characterized as a binding competitor) was added to normal and uremic serum, p-CS, and IS were inhibited to bind HSA. Moreover, Tao et al 32 revealed that 0.6 μmol/min of DHA increased IS removal by 25% in an in vitro HD model.…”
Section: Discussionmentioning
confidence: 99%
“…37 Furthermore, fatty acids have an association constant (Ka) with albumin at 25 C (9.2 × 10 4 to 4.3 × 10 5 M −1 ) that is higher than that of uremic toxins (0.98 × 10 5 M −1 ), allowing them to have a stronger connection with HSA. 38,39 Indeed, de Loor et al 40 observed that when sodium octanoate (a medium chain fatty acid characterized as a binding competitor) was added to normal and uremic serum, p-CS, and IS were inhibited to bind HSA. Moreover, Tao et al 32 revealed that 0.6 μmol/min of DHA increased IS removal by 25% in an in vitro HD model.…”
Section: Discussionmentioning
confidence: 99%
“…Birjandi et al evaluated the effect of varying concentration of human serum albumin in the range from 5 to 100 g/L on the extraction efficiency of polyunsaturated fatty acids by SPME. They found constant extraction efficiencies in the normal range of human serum albumin, but significant differences at very low (<20 g/L) and very high (>70 g/L) albumin concentrations [23]. This should be considered in experimental design to ensure accuracy of total concentrations if they are of interest in a given study.…”
Section: Analytementioning
confidence: 99%
“…This is in agreement with other studies where both kinetic and equilibrium SPME were used for accurate determination of binding constants such as presented in Table 10.1. In another study, SPME was applied to measure human serum albumin binding constants and % PPB of polyunsaturated fatty acids [23]. The affinity constants (K a ) of individual polyunsaturated fatty acids to human serum albumin ranged from 9.2 × 10 4 to 4.3 × 10 5 M −1 , while % PPB ranged from 98.0 to 99.7%.…”
Section: Determination Of Plasma Protein Binding (% Ppb)mentioning
confidence: 99%
“…Birjandi et al. developed a direct immersion SPME method that was coupled to an LC–MS platform (DI‐SPME–HPLC–ESI‐MS) to quantify free FAs in fish and human plasma . SFE, which is based on an increase in the solvation power of a supercritical fluid, is used to effectively extract and separate different lipid species in a sample .…”
Section: Recent Development In Lipidomics Sample Pretreatmentsmentioning
confidence: 99%